Funeral Services Performed in Alevi Villages of the Sivas/Zara Habeş Region - Keleş, Bülent (Journal of Alevism-Bektashism Studies, 2023)
Due to the nature of death and the awareness that everyone will eventually experience it, death and related rituals have been among the prevailing concerns among people throughout history. Based on beliefs tied to remembrance, being remembered, and the afterlife, various religious and/or other rituals are conducted within the confines of the embraced faith, often with the contributions of the deceased’s remaining relatives. While performing these rituals, utmost effort is exerted to adhere to traditional and religious rules. Factors such as the social status of the deceased, their will, and the person conducting the funeral service may lead to minor variations in post-death rituals, but the core of the ritual is kept constant.Communities adhering to the Alevi belief system, influenced by challenging circumstances and striving to minimize potential adversities, have often found themselves in the need to conceal their religious visibility. Consequently, participation in worship has been restricted to include only Alevi community, and limitations have been imposed on the presence of outsiders in ceremonies such as ‘cem.’ However, certain religious rituals that concern the broader community and where Sunni participants are also present have been conducted openly. One of the few religious traditions that make Alevism visible is the ‘Funeral Service.’ Despite the public nature of funeral services, there are some informational gaps regarding the Alevi funeral ritual in many segments of society. As a result of this lack of knowledge, statements expressing surprise and the misconception that there is no actual difference between Alevis and Sunnis have been encountered among Sunni citizens residing in the region we have chosen as the subject of our article. Our study is limited to the funeral services practiced in Alevi villages in the region known as Habeş (Şerefiye) in the Zara district of Sivas province. Within this scope, after providing general information about the Habeş region, funeral services practiced in Alevi villages were compiled with the contributions of individuals known as ‘Hoca’ among Alevites and Alevi communicators. In addition to Alevi source works, conclusions were drawn by benefiting from previous studies. Employing the qualitative research method of social sciences, our study applied a phenomenological approach as its design. Furthermore, participant observation and interview methods were utilized to gather insights from the experiences of individuals we interviewed.
Keywords: Alevism; Funeral in Alevism; Funeral Service; Sivas/Zara Habeş Region; Death; Burial